2013
DOI: 10.1371/journal.pone.0053304
|View full text |Cite
|
Sign up to set email alerts
|

Human Geophagia, Calabash Chalk and Undongo: Mineral Element Nutritional Implications

Abstract: The prime aim of our work is to report and comment on the bioaccessible concentrations – i.e., the soluble content of chemical elements in the gastrointestinal environment that is available for absorption – of a number of essential mineral nutrients and potentially harmful elements (PHEs) associated with the deliberate ingestion of African geophagical materials, namely Calabash chalk and Undongo. The pseudo-total concentrations of 13 mineral nutrients/PHEs were quantified following a nitric-perchloric acid dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 32 publications
1
54
0
4
Order By: Relevance
“…The material preferentially ingested by geophagists is clay. Its ability to form colloids and to adsorb and exchange ions while interacting with the food bolus and the digestive mucosa results in both beneficial and harmful effects [27,28,29]. Clays are used in traditional medicine for rheumatologic pains, skin infections, anaemia, gynaecologic problems or during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The material preferentially ingested by geophagists is clay. Its ability to form colloids and to adsorb and exchange ions while interacting with the food bolus and the digestive mucosa results in both beneficial and harmful effects [27,28,29]. Clays are used in traditional medicine for rheumatologic pains, skin infections, anaemia, gynaecologic problems or during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Les caractéristiques des patients de notre série sont concordantes avec les cas déjà rapportés concernant l'âge [1][2][3][4][5]9], avec des observations de patients relativement jeunes (15 à 25 ans). Par contre, contrairement à Lar et al [10] qui rapportait que plus de 90 % de femmes n'avaient pas atteint le niveau secondaire, 8 sur les 12 patientes de notre série étaient scolarisées dont 5 ayant atteint au moins le secondaire.…”
Section: Discussionunclassified
“…Dans la littérature, elle concerne surtout les enfants et la femme enceinte en Afrique Sub-Saharienne [3]. Malgré son rôle supposé dans le renforcement de la barrière digestive face aux toxines alimentaires, le complexe colloïde (argile, bol alimentaire et muqueuse) met en péril l'équilibre alimentaire des géophages en faveur d'une diminution ou d'une augmentation de la biodisponibilité intestinale de certains minéraux (fer, plomb, zinc, cuivre, arsenic, calcium, magnésium, manganèse, chrome, nickel, potassium, sodium) variable selon le pays, le type d'argile consommée au sein d'un même pays et la quantité ingérée [4][5][6]. Concernant son origine, il existe toujours une controverse sur la géophagie comme cause ou comme conséquence de la carence martiale.…”
Section: Introductionunclassified
“…Several reports have been published concerning this particular topic. For example, the study of Abrahams et al (2013) on the bioavailability of PHEs in two African geophagical materials, Calabash chalk and Undongo, which are commonly used in Nigeria and among the emigrants in different parts of the world, showed that the consumption of these clay soil material does not substantially contribute to PHEs' intake, nor to a better Fe uptake, one of the primary reasons for the geophagy. Conversely, Al-Rmalli et al (2010) showed that a type of clay, sikor, commonly consumed by Bangladeshi women in Bangladesh and in the United Kingdom, especially during pregnancy, may be an important source of As, Cd and Pb intake.…”
Section: Phes' Impact On Human Healthmentioning
confidence: 99%